1987
DOI: 10.1111/j.1528-1157.1987.tb03640.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity in Rat Following Administration of Valproic Acid

Abstract: Chronic injections of valproic acid (VPA), VPA with phenobarbital (PB), and PB were studied for their effects on liver mitochondrial morphology and carnitine metabolism in rats. Mitochondrial enlargement was induced by the administration of VPA (500 mg/kg/day) for a period of 7 consecutive days. The administration of VPA (500 mg/kg/day)-plus-PB (20 mg/kg/day) for 7 days, however, did not induce megamitochondrial formation, but in these livers an unusual increase was observed in the number of liver mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 13 publications
2
28
1
Order By: Relevance
“…In the study of Beghi et al [25] , they reported that carnitine deficiency, which is produced with these antiepileptic drugs, is worth noting and may be a part of a more general biochemical effect of antiepileptic drug therapy on lipid metabolism. However, the significant hypocarnitinemia found in the present study was not detected in the study of Ohtani et al [6] and Sugimoto et al [11] .…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…In the study of Beghi et al [25] , they reported that carnitine deficiency, which is produced with these antiepileptic drugs, is worth noting and may be a part of a more general biochemical effect of antiepileptic drug therapy on lipid metabolism. However, the significant hypocarnitinemia found in the present study was not detected in the study of Ohtani et al [6] and Sugimoto et al [11] .…”
Section: Discussioncontrasting
confidence: 88%
“…In addition, a significant increase of the mean values of GOT in the sera of phenytoin treated cases (P < 0.001) and GPT in the sera of phenobarbital treated cases (P < 0.05) after, in comparison to that before therapy. This finding is supported by the reports of Aldenhovel [28] and Sugimoto et al [11] . Also, the increase in the mean values of pyruvate in phenobarbital treated cases (P < 0.01) and lactate in carbamazepine treated cases (P < 0.01) after, in relation to that before, therapy is in accordance with the findings of Thurston et al [29] and Sugimoto et al [30] .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Experimentally, valproate consistently inhibited @-oxidation and hepatic ketogenesis in vivo (7,8) and in vitro (6,11). In fasted adult rats, the valproate-induced hypoketonemia was not associated with a decreased liver carnitine content or an abnormal hepatic acyl carnitinelfree carnitine concentration ratio (32). In other fasted adult rats receiving valproate, plasma P-hydroxybutyrate levels fell almost 90% despite 2-to 3-fold increases, not decreases, in the hepatic content of total and free carnitine; levels of acyl carnitine were unchanged (8).…”
Section: Discussionmentioning
confidence: 84%